Research on the Influence Construction and Communication Mechanism of Fashion Brands Conducted by Social Media Platforms - Bai, Boyang (Asia Pacific Economic and Management Review, 2024)
With the rapid development of Internet technology, social media has become an important channel for information dissemination, brand building and consumer interaction. The fashion industry, as a field highly dependent on visual display and trendand emotionally connected with consumers, is deeply influenced by the transformation of social media. This study aims to explore the social media platform (such as Instagram, MicroBlog, RED, etc.) how to influence fashion brand influence building and communication mechanism, analysis in the brand story, consumer participation, and the role of market segmentation strategy, effective use of social media resources for fashion brands to provide theoretical support and strategy advice.